91. Impaired interhemispheric processing in early Huntington's disease: A transcranial magnetic stimulation study. Issue 4 (April 2016) - Bocci, T.; Hesgens, M.; Di Rollo, A.; Barloscio, D.; Parenti, L.; Priori, A.; Sartucci, F.
Abstract : A growing number of papers have recently investigated changes in interhemispheric connectivity in HD, although little is known about their temporal relation with clinical features and electrophysiological parameters. In this study we evaluated for the first time interhemispheric connectivity in Huntington's disease (HD) by using a transcranial magnetic stimulation (TMS) protocol. We evaluated ipsilateral silent period (onset latency, iSPOL, and duration, iSPD) and transcallosal conduction time (TCT) in early manifest HD patients compared with sex and age-matched healthy volunteers; then, in HD group, we correlated TMS data with cognitive (MMSE), genetic (CAG-length), and clinical (UHDRS-I) scores. Compared with healthy volunteers, patients showed a marked decrease of iSPD, paralleled by a significant lengthening of iSPOL and TCT ( p  < 0.01). The impaired interhemispheric processing in HD significantly correlated with clinical (Mini-Mental Examination score and UHDRS-I) and genetic (CAG-length) data ( p  < 0.05). Callosal processing is impaired in early manifest HD; the interhemispheric disruption may have, at least in part, implications for the impaired sensorimotor integration and motor control, in addition to the defective gating of peripheral afferent input. Our results prompt further research in the whole field of hyperkinetic movement disorders, in which data about TMS and interhemispheric excitability changes are still lacking.